Development Instrument Independence Study in Chemistry Learning Using Exploratory Factor Analysis (EFA) and Factor Analysis Confirmatory (CFA) - Aurelia Revi Pusbelina; Hari Sutrisno (Jurnal Penelitian Pendidikan IPA, 2025)
This study examines the early development of student learning independence instruments in chemistry learning using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The purpose of this study is to develop a learning independence instrument that specifically measures chemistry learning independence. A quantitative survey approach was used in this investigation. The research sample used was 642 students of class XI MIPA 1 from 10 State Senior High Schools in Bantul Regency, then the sample determination was carried out using a random sampling technique. The instrument used was a questionnaire consisting of 16 items. Sixteen items on a 5-point Likert scale representing students' perceptions of themselves were used to collect data. Exploratory Factor Analysis (EFA) is the data analysis method used. The learning independence questionnaire filled out by 642 respondents was analyzed using the JASP for Windows 10 application. All items from the EFA analysis results were acceptable because they had a factor value of >0.3. While the results of the CFA test showed that all items were valid with a p value <0.05; *** significance and SLF value ≥ 0.5 and reliable with CR value ≥ 0.70 and AVE value of at least 0.5. The results obtained prove that the instrument is valid and can be used to measure the independence of learning chemistry.